Multi-gene analysis of the Russula crown clade (Russulales, Basidiomycota) revealed six new species and Alboflavinae subsect. nov. from Fagaceae forests in China - Niu, Caiyun; Liu, Tiezhi; Zhao, Shiyi; Ren, Jing; Zhao, Yi; Kang, Xia; Qin, Weiqiang; Xie, Xuejiao; Zhang, Xu; Wei, Tiezheng; Tian, Jinghua; Li, Xiao; et al. (Frontiers in Plant Science, 2024)
The crown clade is one of two major groups in the Russula subg. Russula. An analysis of Chinese samples was performed based on morphology, ITS and multi-gene phylogenies of 28S nrLSU, 16S mtSSU, rpb1, rpb2 and tef1-α. The results supported the independence of six new species: Russula alboflava (sect. Amethystinae), R. chrysantha (subsect. Chamaeleontinae), R. liyui (subsect. Laricinae), R. lutescens (subsect. Olivaceinae), R. paraxerampelina and R. prunicolor (subsect. Xerampelinae) from Fagaceae forest habitats. Subsect. Alboflavinae was newly proposed in sect. Amethystinae. Members of the new subsection include R. alboflava, R. burlinghamiae, and possibly R. ballouii. Our analyses also supported the claim that two species of R. fulvograminea (subsect. Laricinae) and R. subrubens (subsect. Xerampelinae) have a Eurasian distribution. Habitat and primary hosts of the main phylogenetic clades within related subsections were summarized and discussed.